2013
DOI: 10.1007/s10802-013-9828-7
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Vulnerabilities as Mediators between Emotional Abuse and Depressive Symptoms

Abstract: This study tested whether childhood parental emotional abuse and peer emotional bullying serve as antecedents of depression in adolescence and identified the cognitive mechanisms involved in this process. It was hypothesized that the experience of emotional abuse would predict depressive symptoms via development of rumination and negative inferences. A 3-wave longitudinal study was carried out with 998 adolescents (471 girls and 526 boys) between 13 and 17 years of age. Results showed that emotional abuse by p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 65 publications
3
34
0
1
Order By: Relevance
“…The results presented by Paredes & Calvete, 37 which we rated to be moderate quality, suggests that a certain cognitive vulnerability, brooding, may be a modifiable predictor of depression. This was a three-phase longitudinal study of 998 adolescents aged 13 to 17.…”
Section: Resultsmentioning
confidence: 81%
“…The results presented by Paredes & Calvete, 37 which we rated to be moderate quality, suggests that a certain cognitive vulnerability, brooding, may be a modifiable predictor of depression. This was a three-phase longitudinal study of 998 adolescents aged 13 to 17.…”
Section: Resultsmentioning
confidence: 81%
“…In a long-term prospective cohort study, Widom and colleagues (2008) found that adults who had experienced court-documented abuse and neglect in childhood ( n = 496) reported significantly higher rates of additional traumas by age 40 relative to a socioeconomically matched control group with no such history ( n = 396) (Widom, Czaja, & Dutton, 2008). Similarly, other longitudinal studies have found that individuals exposed to sexual or physical abuse early in life are significantly more likely to experience re-victimization later in life (Culatta, Clay-Warner, Boyle, & Oshri, 2017; Fisher et al, 2015; Noll, Horowitz, Bonanno, Trickett, & Putnam, 2003; Padilla Paredes & Calvete, 2014; Rich, Gidycz, Warkentin, Loh, & Weiland, 2005). …”
Section: Introductionmentioning
confidence: 71%
“…Providing more proximal assessments of childhood abuse are four studies featuring either child samples (Gibb & Abela, , n = 140; Gibb, Stone, & Crossett, , n = 100; Mezulis, Hyde, & Abramson, , n = 289) or an adolescent sample (Padilla Paredes & Calvete, , n = 1,316). Negative inferential styles have been associated with parental CEA (Gibb & Abela, , n = 140; Padilla Paredes & Calvete, ) and peer victimization in youth (Mezulis et al., ; Padilla Paredes & Calvete, ). There is some evidence that negative inferential styles may be particularly related to relational victimization (i.e., victimization intended to inflict harm on an individual's social standing and peer relationships) rather than overt victimization (i.e., direct physical victimization, including hitting and kicking; Gibb et al., ).…”
Section: Empirical Evaluations Of the Hopelessness Theorymentioning
confidence: 99%